Split obturator: An innovative approach - Sunit K Jurel; Raghuwar D Singh; Durga Shanker Gupta (Wolters Kluwer Medknow Publications, 2011)
A palatal prosthesis can improve function by closing the palatal defect, preventing regurgitation, and improving swallowing and speech. Although techniques have been previously described for fabrication of palatal obturator, but there has not been any technique to devise an obturator for a patient with palatal defect with a quadhelix orthodontic appliance overlying it. One cannot wait in such patients for completion of lengthy orthodontic treatment and then think of devising prosthesis as the patient cannot carry out normal functions like swallowing and speech without the closure of defect. This article focuses on an innovative method of fabricating a palatal obturator which aims at restoring the above-mentioned functions along with improving aesthetics. It also enables us to devise the fabrication of prosthesis in two parts for easy insertion and removal and as well as to be self-cleansable. Such prosthesis would markedly improve patient psychology and confidence.